Protective effects of pentoxifylline in retinal ischemia/reperfusion injury - Demir, T; Ulas, F; Ozercan, I; Ilhan, N; Celiker, U; Yasar, MA (Karger, 2003)
We studied the effect of pentoxifylline on retinal lipid peroxidation and histopathologic changes due to ischemia/reperfusion (I/R). A total of 15 pigmented male guinea pigs were divided into 3 equal groups as control, sham and treatment groups. After application of high intraocular pressure for 90 min for the induction of retinal ischemia, 24-hour reperfusion was established in the sham and treatment groups. In the treatment and sham groups, either 45 mg/kg of pentoxifylline or saline was given 3 times at 8-hour intervals. Biochemical assay and histopathologic evaluation were performed on one randomly selected eye of each animal which was enucleated at the end of the reperfusion period, and retinal malondialdehyde (MDA) levels and thickness of the retinal tissue were determined for each group. The mean MDA level of the sham group was significantly higher versus the control and treatment groups (p < 0.001). When compared with the control group, the mean MDA level of the treatment group was slightly higher, but the difference was not statistically significant (p > 0.05). In comparison with the control group there was a significant increase in the thickness of the retina in the sham group (p < 0.0001), and no significant difference was found in the retinal thickness of the treatment group (p > 0.05). Pentoxifylline might have a preventive effect on the I/R injury of the retina. Copyright (C) 2003 S. Karger AG, Basel.
Keywords: pentoxifylline; retinal ischemia and reperfusion